Peran Orang Tua dan Guru Les dalam Pembelajaran IPA di masa Pandemi Covid-19 - Nina Khaerunnisa; Jumadi Jumadi; Hafizha Kurnia Indahsari; Ayu Rischi Utami (Postgraduate, University of Mataram, 2022)
The implementation of online learning activities makes parents take part in the activities of the science learning process. It is not uncommon for those who include their children to take part in tutoring activities so that they can study well even though they are in a COVID-19 pandemic condition. This study aims to determine the role of parents and tutors in science learning during the COVID-19 pandemic. The research method used in this study is a qualitative descriptive method with a phenomenological type of research. The research sample consisted of 10 people consisting of 5 junior high school students, 2 parents, 2 tutors, and 1 science teacher at school. Collecting data using observation, interviews, and questionnaires. The results of the study stated that the role of parents in science learning during the Covid-19 period was to accompany, supervise, establish communication, direct, motivate, and provide facilities (facilitators). The role of the tutor in science learning during the COVID-19 period is to assist, assist the learning process, direct, and evaluate. Parents and tutors have a closely related role in science learning, namely helping each other, accompanying, and directing students so that they can continue to study well during the covid-19 pandemic